PENERAPAN PROTOKOL KESEHATAN COVID-19 PADA RUANG PUBLIK DI JAWA TENGAH - Arif Sofianto; Mursid Zuhri; Lita Febrian; Okki Chandra Ambarwati (Jurnal Kesehatan Masyarakat (Undip), 2022)
Covid-19 cases in Indonesia tend to increase, and several studies show that there is still a lack of public awareness on implementing health protocols. Public spaces have a greater potential for transmission than private spaces, so it is important to ensure the implementation of health protocols. The purpose of this study was to determine the potential for community behavior on implementing health protocols in public spaces, as well as how to improve efforts that need to be made. This type of research is descriptive with a mixed method quantitative and qualitative, and its applied research. This research was conducted using a survey technique involving 2,894 respondents spread throughout Central Java. The sample is probability sampling, determined by the technique of multistage random sampling and cluster random sampling. The instrument of this research is a semi-closed questionnaire which is given through google form media. The analysis in this study uses descriptive statistical techniques, as well as qualitative analysis of simultaneous models. This study concludes that public areas must be watched out for because they have the potential to create a fairly high level of the crowd, but the implementation of the covid-19 health protocols has not been optimal, especially tourist and entertainment places, public transportation, and traditional markets. Several places with high potential for visits, such as workplaces, places of worship, culinary places, and socio-religious celebrations/rituals, also need to improve the implementation of health protocols.